Addicon: “We are logistics” - Wee, Chow Hou (2022)
One morning in January 2001, while using his Honma’s driver, Benjamin was about to execute his first shot at Laguna Golf Course when a self-discourse resulted in an uncharacteristic sliced teeshot. It had been already three months since he left his job as a General Manager of a large logistics company and his wife was unaware that he was jobless. Without fail, each morning Benjamin would put on his smart office attire and “go to work”, never giving away any clue of his career plight. Instead, he would simply head to his Country Club to play golf. The thought of setting up his own business did cross his mind, but Benjamin had reservations about being his own boss at that time. This was largely because his son was only three years old and so he naturally preferred a more secure income by working for a large logistics company rather than bearing the risk of being self-employed. Over a period of time, however, Benjamin began to realize how much he wanted to run his own business. He simply needed to trust in his capabilities and passion in logistics. Deep down within him, he knew it was time to take the plunge deeper into the competitive logistics world! Benjamin eventually plucked up the courage and established Addicon Logistics Management Pte Ltd in April 2001.